Sonographic evaluation of penile trauma - Bhatt, S; Kocakoc, E; Rubens, DJ; Seftel, AD; Dogra, VS (Wiley, 2005)
Objective. The purpose of this presentation is to illustrate the normal sonographic anatomy of the penis and various imaging manifestations of penile trauma. Methods. Penile trauma cases were collected and reviewed retrospectively from our archive. Results. The normal sonographic anatomy of the penis and various pathologic conditions of patients with penile trauma are discussed. Conclusions. Sonography (especially with color Doppler sonography) is a useful imaging method for evaluating penile anatomy and various pathologic features in patients with penile trauma.
Keywords: color Doppler sonography; penile anatomy; penile trauma; priapism; sonography